From hand-held radio to ride-hailing platforms: Research on a local technical network of taxi drivers in China - Zhang, Wenjie; Tang, Wanxin; Yu, Tiantian; Wang, Hongzhe (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2023)
This paper investigates how Chinese taxi drivers utilize low-tech equipment, such as handheld radios and mobile phone services, to form local ride-hailing networks. Previous studies have analyzed how Internet platforms like Didi Chuxing have reshaped labor relations through technology and policies, but they have ignored the fact that outside metropolitan areas, traditional technological solutions, such as on-call radio platforms, have not been replaced by the rapidly expanding ride-hailing platforms. Therefore, to outline China’s diverse ICT practice environment, this paper focuses on a case study in two Chinese towns (Laizhou, Shandong; Ziyang, Sichuan), shifting the attention from metropolitan areas to neglected fourth- and fifth-tier cities. After reviewing the previous advancements in mobile communication technology, we discuss the economic, cultural, and social motivations behind the use of ‘low-tech’ devices and cooperative services by the Chinese taxi drivers in question.